Proyecto fotográfico Bekanwe" - Planteamiento de una exposición fotográfica" - Horna Horna, Pedro Enrique (2020)
This project is a visual-anthropological essay that uses documentary photography as its main tool to show a pure Shipibo Konibo community’s actual way of life. This way, it is meant to break the pre conceived ideas that a metropolitan society can develop about similar human groups, from their own and -at the same time- foreign ones.